Emission Caps and Investment in Green Technologies - Biais, Bruno; Landier, Augustin (Review of Financial Studies, 2026)
Abstract We study the interaction between firms, which can invest in green technologies, and a government, which can impose emission caps but has limited commitment power. Investment in green technologies generates innovation spillovers, reducing the cost of further investments. Spillovers generate intertemporal strategic complementarities between firms and government, and equilibrium multiplicity. In a “green equilibrium”, firms, anticipating caps, invest in green technologies, which reduces the cost of further investment, making the government willing to cap emissions. In a “brown equilibrium”, firms, anticipating no caps, don’t invest, so green technologies remain costly and the government gives up on emission caps.